2022
DOI: 10.1212/nxi.0000000000001162
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Cell-Based Assay for Alpha-3 Nicotinic Receptor Antibodies Detects Antibodies Exclusively in Autoimmune Autonomic Ganglionopathy

Abstract: Background and ObjectivesAutoantibodies against α3-subunit–containing nicotinic acetylcholine receptors (α3-nAChRs), usually measured by radioimmunoprecipitation assay (RIPA), are detected in patients with autoimmune autonomic ganglionopathy (AAG). However, low α3-nAChR antibody levels are frequently detected in other neurologic diseases with questionable significance. Our objective was to develop a method for the selective detection of the potentially pathogenic α3-nAChR antibodies, seemingly present only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…Karagiorgou and colleagues recently published their work on a cell-based assay (CBA) for α3-nAChR in the journal Neurology Neuroimmunology and Neuroinflammation [9].…”
Section: Doctor What About These Antibody Results?mentioning
confidence: 99%
“…Karagiorgou and colleagues recently published their work on a cell-based assay (CBA) for α3-nAChR in the journal Neurology Neuroimmunology and Neuroinflammation [9].…”
Section: Doctor What About These Antibody Results?mentioning
confidence: 99%
“…McKeon et al reported that serum anti-gAChR antibodies were present in 155 of 15,000 patients (1.03%) with suspected paraneoplastic autoimmune neurological syndrome but in only 1 of 173 healthy subjects (0.58%) ( 21 ). More recently, 0% of 2,628 patients with non-AAG neurological diseases were positive for antibodies to α3-nAChR ( 22 ). These reports suggest that anti-gAChR antibodies are usually undetectable or present at very low levels in the serum ( 16 , 19 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using live CBA, Karagiorgou et al reported that they detected only antibodies to cell-exposed epitopes of the antigen. 16 Until their study, the expression of neuronal nicotinic AChR by transfected cells has usually been low, and the high sensitivity required for the corresponding CBA could not be achieved. These investigators were able to overcome this problem by using two chaperones in combination with nicotine to increase gAChR expression on the cell surface, thereby improving the sensitivity of the antibody assay.…”
Section: Autoantibodies Against Gachr In Patients With Aag Detection ...mentioning
confidence: 99%